Methods to Relieve Heat Stress for Florida Dairies - Izabella M. Toledo; Ray A. Bucklin; Geoffrey E. Dahl; David K. Beede (EDIS, 2019)
The hot and humid weather in Florida affects dairy cattle performance throughout the year, and producers who hope to achieve optimum production from their dairy cows must provide them with relief from heat and humidity. This 4-page fact sheet written by I. M. Toledo, G. E. Dahl, R. A. Bucklin, and D. K. Beeke and published by the UF/IFAS Department of Agricultural and Biological Engineering describes several cooling strategies to alleviate heat stress in dairy cattle. http://edis.ifas.ufl.edu/ae022